Investigation of the formation mechanism of mesophase pitch based on the evolution of molecular structure - Yan Yang; Qian Li; Pingping Zuo; Shijie Qu; Fangfang Qin; Wenzhong Shen (Fuel, 2026)

BRCA-CN: a blockchain-based framework to support public variant databases sharing in multi-center community for diagnostic reference and China regulatory science - Shoufang Qu; Rongzhi Liu; Shisen Li; Chuanfeng Huang; Yingqian Zhang; Xuan Gao; Pingping Dai; Chao Xu; Rutao Yang; Xuchao Li; Guojun Ouyang; Kang Shao; et al. (Human Genetics, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

A GNSS PPP integrity monitoring algorithm based on ARKF and MHSS - Ershen Wang; Tengli Yu; Xinhui Sun; Pingping Qu; Tingyu Chen; Xuebao Hong; Song Xu; Zexin Liu (Advances in Space Research, 2025)

Preparation of pitch-based carbon fiber from medium coal tar pitch refined by wash oil - Pingping Zuo; Shaobo Fu; Xiaoqiang He; Hongxian Niu; Shijie Qu; Wenzhong Shen (Fuel, 2025)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Satellite navigation signal quality monitoring algorithm based on DBO-SVM - Ershen Wang; Yilin He; Tengli Yu; Liang Liu; Song Xu; Pingping Qu; Tao Pang (Advances in Space Research, 2024)

Heat transfer performance study of Cu-ethanol/ethylene glycol/propylene glycol-water nanofluids in a wavy-walled tube heat exchanger - Liang Zhang; Jiabai Song; Pingping Qu; Shuangzhu Wang; Huimin Zhang; Hairui Wang; Hongfa Liu; Taiyan Lu (Journal of Environmental Chemical Engineering, 2024)

Enhancing methanol tolerance of Thermomyces lanuginosus lipase by rational design and biodiesel production through one-step feeding of methanol - Pingping Qu; Raudah Lazim; Dongdong Li; Rui Xu; Fei Wang; Xun Li; Yu Zhang (Journal of Cleaner Production, 2024)

Exploring the association between air pollution and Parkinson’s disease or Alzheimer’s disease: a Mendelian randomization study - Pingping Ning; Xingzhi Guo; Qiumin Qu; Rui Li (Environmental Science and Pollution Research, 2023)

Cellular Heterogeneity Facilitates the Functional Differences Between Hair Follicle Dermal Sheath Cells and Dermal Papilla Cells: A New Classification System for Mesenchymal Cells within the Hair Follicle Niche - Yuyang Gan; Hailin Wang; Lijuan Du; Kaitao Li; Qian Qu; Weiwen Liu; Pingping Sun; Zhexiang Fan; Jin Wang; Ruosi Chen; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2022)

A cytokinin-activation enzyme-like gene improves grain yield under various field conditions in rice - Changgui Wang; Guokui Wang; Yang Gao; Guihua Lu; Jeffrey E. Habben; Guanfan Mao; Guangwu Chen; Jiantao Wang; Fan Yang; Xiaoqiang Zhao; Jing Zhang; Hua Mo; et al. (Plant Molecular Biology, 2020)

Interactions between ultraviolet radiation exposure and phosphorus limitation in the marine nitrogen‐fixing cyanobacteria Trichodesmium and Crocosphaera - Zhu Zhu; Feixue Fu; Pingping Qu; Esther Wing Kwan Mak; Haibo Jiang; Ruifeng Zhang; Zhuoyi Zhu; Kunshan Gao; David A. Hutchins (Limnology and Oceanography, 2020)
Increased stratification and mixed layer shoaling of the surface ocean resulting from warming can lead to exposure of marine dinitrogen (N 2 )‐fixing cyanobacteria to higher levels of inhibitory ultraviolet (UV) radiation. These same processes also reduce vertically advected supplies of the potentially limiting nutrient phosphorus (P) to N 2 fixers. It is currently unknown how UV inhibition and P limitation interact to affect the biogeochemical cycles of nitrogen and carbon in these biogeochemically critical microbes. We investigated the responses of the important and widespread marine N 2 ‐fixing cyanobacteria Crocosphaera (strain WH0005) and Trichodesmium (strains IMS 101 and GBR) to UV‐A and UV‐B under P‐replete and P‐limited conditions. Growth, N 2 fixation, and carbon dioxide (CO 2 ) fixation rates of Trichodesmium IMS 101 and Crocosphaera were negatively affected by UV exposure. This inhibition was greater for Trichodesmium IMS 101 than for Crocosphaera , which fixes N 2 only during the night and so avoids direct UV damage. Negative effects of UV on both IMS 101 and Crocosphaera were less in P‐limited cultures than in P‐replete cultures. In contrast, no UV inhibition was observed in GBR, regardless of P availability. UV inhibition was related to different amounts of UV‐absorbing compounds produced by these isolates. Responses to UV radiation and P availability interactions were taxon‐specific, but our results indicated that in general, UV radiation effects on Trichodesmium and Crocosphaera range from negative to neutral. UV inhibition and its interactions with P limitation may thus have a substantial influence on the present day and future nitrogen and carbon cycles of the ocean.

Responses of the large centric diatom Coscinodiscus sp. to interactions between warming, elevated CO 2 , and nitrate availability - Pingping Qu; Feixue Fu; David A. Hutchins (Limnology and Oceanography, 2018)
Marine ecosystems are facing multiple anthropogenic global changes, including ocean acidification, warming, and reduced nutrient supplies. Together, these will challenge phytoplankton including large centric diatoms such as Coscinodiscus sp., a group that is important to ocean food webs and carbon export. We investigated the interactive effects of warming, elevated CO 2 , and nitrate availability on Coscinodiscus growth, elemental stoichiometry, and Fe and C uptake rates in a four‐treatment factorial experiment combining two CO 2 levels (∼400 ppm and 800 ppm) and two temperatures (16°C and 20°C) across seven nitrate concentrations (1–100 μ mol L −1 ). Higher temperatures led to higher maximum growth rates ( μ max ), but also higher half‐saturation constants for nitrate ( K 1/2 ), while elevated CO 2 increased K 1/2 only at the warmer temperature. Lower μ max / K 1/2 ratios under warming and rising CO 2 indicated a higher nitrate requirement at these conditions. High temperature decreased cellular P and Si contents and consequently increased N : P and C : Si ratios, especially at ambient CO 2 . Fe : C uptake ratios responded positively to lower nitrate levels, lower CO 2 , and warming. Significant interactions between nitrate availability and temperature or CO 2 were observed for specific growth rates, chlorophyll a and Si contents, Fe : C, N : P, and Si : C, while temperature and CO 2 interactions were only significant for μ max / K 1/2 and cellular P content. The mutual interactions among CO 2 concentrations, temperature, and nitrate supply may all affect future growth, physiology, and carbon export by Coscinodiscus sp., however, in general warming and nitrate availability appear to be more influential than CO 2 .

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)